The Fran that time forgot - Benton, Jim (Benton, Jim. Franny K. Stein, mad scientist, 2005)
When her embarrassing middle name is revealed at school, mad scientist Franny K. Stein experiments with time in order to return to the past and give herself a more dignified name.